Creating a Randomized Residential Cluster Using Neural Network Method - Tirta Prawisuda; Albert Van Otto; Taufiq Radityadji (Ultimatics : Jurnal Teknik Informatika, 2013)
Along with the city growth around the world, residential cluster also grows as a more preferable choice of housing. The high amount of residential cluster makes it inevitable for each cluster to looks the same with the other cluster. This paper will try to develop an idea so each cluster will look different. Index Terms—Artifical intelligence, computing, neural network, residential cluster.